Front Cover: Photochemical Mechanism of an Atypical Algal Phytochrome (ChemBioChem 10/2018). (27th April 2018) - Choudry, Uzma; Heyes, Derren J.; Hardman, Samantha J. O.; Sakuma, Michiyo; Sazanovich, Igor V.; Woodhouse, Joyce; De La Mora, Eugenio; Pedersen, Martin N.; Wulff, Michael; Weik, Martin; Schirò, Giorgio; Scrutton, Nigel S.
Abstract : The front cover picture shows the visible and infra‐red transient absorption data and bilin structures for the photoconversion of a novel phytochrome from Dolihomastix tenuilepis between orange‐ and far‐red‐absorbing states. The unique ability of phytochromes from some algae to respond to multiple wavelengths of light has made them attractive targets for optogenetic applications. We used a combination of time‐resolved visible, IR, and X‐ray scattering techniques across picosecond to second timescales to map the photochemical mechanisms and structural changes in phytochromes. The photocycle for this atypical phytochrome is complex, thus it is necessary to combine outcomes from a range of biophysical approaches in order to unravel all the photochemical and macromolecular processes that are behind biological light‐mediated signalling in multi‐domain photoreceptor proteins. More information can be found in the full paper by N. S. Scrutton et al. onpage 1036 in Issue 10, 2018 (DOI:10.1002/cbic.201800016 ).